An infant case of intraoral penetrating injury with a toothbrush causing retropharyngeal and upper mediastinal emphysema - Kei Jitsuiki; Ayako Hashimoto; Toshihiko Yoshizawa; Youichi Yanagawa (Wolters Kluwer Medknow Publications, 2017)
A 2-year-old male child who was running and fell with a toothbrush in his mouth suffered an injury to the inside of his right cheeks. His mother noticed that the toothbrush had impaled his mouth, and removed it. On arrival, a wound was observed on the right cheeks and palate. His general condition was good. However, computed tomography revealed emphysema from the left side of epipharynx to the upper mediastinum. This patient shows the importance of not only checking the medical history and performing a physical examination but also performing an imaging examination.